Modelling of biomass milling - Newbolt, Gary S. (2018)
Strategies to combat climate change focus on every industry and has led to government policies to reduce electricity generation through coal combustion. Switching to biomass provides an opportunity to use infrastructure constructed for coal combustion with carbon neutral fuels; however, the process of grinding biomass pellets as fuel in pulverised fuel combustion is not well known. 1% of energy generated at a power plant is utilised to achieve the required size for the fuel. Improvements in the understanding of biomass pellet milling could lead to optimisation of operating conditions and minimisation of energy consumption. The process could aid generators determine appropriate fuels and costs for each; this represents a potential opportunity to elongate the life of current power stations, which is more cost effective than construction of new biomass specific plants.